Exploring the Development of Writerly Identity Through the Use of Blogging - Hindley, David; Clughen, Lisa (Journal of Academic Writing, 2018)
This paper discusses implementation of blog writing as a formative assessment within a final year undergraduate module. Drawing on students’ perceptions and experiences, it proposes that blogging offers a more inclusive writing genre for Higher Education than traditional forms of academic scholarship.